2001
DOI: 10.1161/hs1201.099714
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Classification of HITS Into Artifacts or Solid or Gaseous Emboli by a Wavelet Representation Combined With Dual-Gate TCD

Abstract: Background and Purpose-Transcranial Doppler (TCD) can detect high-intensity transient signals (HITS) in the cerebralcirculation. HITS may correspond to artifacts or solid or gaseous emboli. The aim of this study was to develop an offline automated Doppler system allowing the classification of HITS. Methods-We studied 600 HITS in vivo, including 200 artifacts from normal subjects, 200 solid emboli from patients with symptomatic internal carotid artery stenosis, and 200 gaseous emboli in stroke patients with pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 51 publications
2
37
0
1
Order By: Relevance
“…Transcranial Doppler ultrasound (TCD) monitoring has now shown that signals identified in the Fast Fourier Transformation (FFT) of the spectrum may represent ‘microembolic’ particles and are very often detectable in patients with potential sources of embolism, although they hardly ever cause any associated clinical events [22,23,24,25,26,27,28,29,30]. Thus, these signals should be described as high-intensity transient signals (HITS) within the Doppler spectra rather than microembolic signals.…”
Section: Imaging and Ultrasound Monitoring Data Shows That The Prevalmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcranial Doppler ultrasound (TCD) monitoring has now shown that signals identified in the Fast Fourier Transformation (FFT) of the spectrum may represent ‘microembolic’ particles and are very often detectable in patients with potential sources of embolism, although they hardly ever cause any associated clinical events [22,23,24,25,26,27,28,29,30]. Thus, these signals should be described as high-intensity transient signals (HITS) within the Doppler spectra rather than microembolic signals.…”
Section: Imaging and Ultrasound Monitoring Data Shows That The Prevalmentioning
confidence: 99%
“…Patients with atrial fibrillation, those with coronary atherosclerotic heart disease with ejection fractions of <30%, dilated cardiomyopathy, and valvular heart disease have the highest frequency. However, quite often these signals are produced by microgaseous cavitations that can be differentiated from solid thromboembolic material detected during and shortly after cardiac surgery [26, 27]. Many HITS are detected in the MCAs and in the lumen of the aorta during and after cardiac surgery when patients are monitored using TCD and transesophageal echocardiography [41,42,43,44,45].…”
Section: Imaging and Ultrasound Monitoring Data Shows That The Prevalmentioning
confidence: 99%
“…Emboli detection has been improved by using dual-gate, reference-gate, and multifrequency Doppler, which help distinguish artifact from real emboli. 11,12 In this study we showed that when compared with spectral TCD, the transcranial PMD detected more microbubble signals, thereby improving the diagnostic accuracy of PMD in detecting cardiac right-to-left shunt.…”
Section: Discussionmentioning
confidence: 70%
“…Emboli detection has been improved by using dual-gate, reference-gate, and multifrequency Doppler, which help distinguish artifact from real emboli. 11,12 In this study we showed that when compared with spectral TCD, the transcranial PMD detected more microbubble signals, thereby improving the diagnostic accuracy of PMD in detecting cardiac right-to-left shunt.The reason for the increased yield of MBS counts with transcranial PMD is increased sampling due to the simultaneous insonation of both MCA and ACA, allowing detection of emboli traveling in either artery. This effect persists after Valsalva maneuver.…”
mentioning
confidence: 70%
“…7 and 9 shows how, in the case of simple events, there are clear differences between the characteristics of embolic signals and artifacts. Embolic signals show a progressive time delay between their arrivals in adjacent gates and are unidirectional, and artifacts appear simultaneously in all gates (including the gate placed outside the vessel) and are bidirectional [8], [11], [14], [22]- [27]. The inclusion of these properties as inputs into our expert reasoning system will further enhance its high performance levels.…”
Section: Discussionmentioning
confidence: 99%